Organic agriculture practises and approaches to certification of Organic agriproducts: Review article - Chumak, K.; Soytong, K.; Song, J. J.; Mitrokhin, M. (My University, 2024)
Organic certification has encouraged for reliable the consumer demand to get safety food. Association of Agricultural Technology in Southeast Asia (AATSEA) has started irganically certified in the year of 2015 by following the organic standard from many certify bodies eg., International Federation of Organic Agriculture Movements (IFOAM) by BioAgriCert, organic USDA etc. The main target is to examine organic production without application of agrochemicals (chemical fertlizers, chemical pesticides and other synthrtic chemicals) through environmental protection surrounding of soil, water, air and biodiversity for sustainability. In 2022 AATSEA has proposed an dynamic evolution of modern organic agriculture for certification. AATSEA Organic standard is approved by the committee which concerns to the final organic products will not detect toxic agrochemicals, formalin, nitrate/nitrite, non-GMO, low standard of heavy metals as well as Escherichia coli, Samonella sp. The burgeoning logistics and supply chains for agricultural products across Eurasia necessitate robust interaction and expert dialogue among relevant certification bodies. This is crucial for fostering harmonisation and mutual recognition of organic products between RusQuality, Russia and AATSEA Organic certification.
Keywords: AATSEA; Organic certified; RusQuality